2022
DOI: 10.1186/s12877-022-03704-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of sarcopenia in community-dwelling older adults at risk of malnutrition

Abstract: Background There is an increasingly strong association between sarcopenia and malnutrition in research findings. We aimed to determine the prevalence and factors associated with sarcopenia in community-dwelling older adults (≥ 65 years) at risk of malnutrition based on Malnutrition Universal Screening Tool (MUST). Methods This was a cross-sectional study of 811 participants. Participants were recruited from the general population, community centers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
18
1
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 76 publications
5
18
1
3
Order By: Relevance
“…Further, it was also evident in this review that the prevalence of sarcopenia was higher in men than women. This corresponds to findings from studies by Yuenyongchaiwat et al 38 and Chew et al 66 Another study by Du et al 67 conducted among 631 subjects supported this statement by stating that levels of testosterone and insulin‐like growth factor‐1 levels decreased significantly in older males, which caused rapid loss of muscle mass and strength compared to their female counterparts. However, Wang et al 56 and Samper‐Ternent et al 49 from the current study reported otherwise, stating that the prevalence of sarcopenia among females was higher than in males, and there were also other studies supporting this outcome 68,69 .…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Further, it was also evident in this review that the prevalence of sarcopenia was higher in men than women. This corresponds to findings from studies by Yuenyongchaiwat et al 38 and Chew et al 66 Another study by Du et al 67 conducted among 631 subjects supported this statement by stating that levels of testosterone and insulin‐like growth factor‐1 levels decreased significantly in older males, which caused rapid loss of muscle mass and strength compared to their female counterparts. However, Wang et al 56 and Samper‐Ternent et al 49 from the current study reported otherwise, stating that the prevalence of sarcopenia among females was higher than in males, and there were also other studies supporting this outcome 68,69 .…”
Section: Discussionsupporting
confidence: 85%
“…83 On the other hand, being malnourished or at risk of malnutrition is also a contributing factor to sarcopenia. Chew et al 66 also reported sarcopenia to be significantly associated with a higher risk of malnutrition among 694 older people. Older people are often diagnosed with protein-energy malnutrition (PEM), with physiological and psychosocial contributing factors.…”
Section: Discussionmentioning
confidence: 98%
“…Most global literature found a significant association between males and sarcopenia like our study although there are some studies showed an association between females and sarcopenia instead. (18, 19, 21, 22) Nonetheless, this highlights likely unique gender differences in developments of sarcopenia. (21, 58) It has been postulated that myostatin causing catabolism in males and reduced IGF-1 leading to anabolic decline in females have a role in the sex differences in sarcopenia development.…”
Section: Discussionmentioning
confidence: 98%
“…(21) Another study reported sarcopenia prevalence of 76% among community ambulant adults aged 65 and above who were at medium or high risk of malnutrition. (22) The prevalence of sarcopenia in primary care and specialist outpatient clinics ranged from 27.4% in patients aged 60-89 years old with Type 2 Diabetes Mellitus using AWGS criteria, to 44% in patients aged 65 and above based on SARC-F questionnaire only. (19, 25)…”
Section: Introductionmentioning
confidence: 99%
“…Low AC may also relate to sarcopenia and lower bone mass, which may also contribute to the poor outcomes of hip fractures [ 12 , 13 ]. In a study focusing on community-dwelling older adults at risk of malnutrition, there is a significant and prevalent association between sarcopenia and lower calf circumference [ 14 ].…”
Section: Discussionmentioning
confidence: 99%